2021
DOI: 10.3389/fmolb.2020.627842
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Glutamine: SARS-CoV-2 Triggered Pathogenesis via Metabolic Reprograming of Glutamine in Host Cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, as coronavirus disease 2019 (COVID-19) pandemic, has killed more than a million people worldwide, and researchers are constantly working to develop therapeutics in the treatment and prevention of this new viral infection. To infect and induced pathogenesis as observed in other viral infections, we postulated that SARS-CoV-2 may also require an escalation in the anabolic metabolism, such as glucose and glutamine, to support its energy and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 135 publications
3
31
0
Order By: Relevance
“…Prophylactic glutamine supplementation is recommended to those in high-risk groups; however, glutamine supplementation after the infection should be carefully considered. Glutamine supplementation may favor SARS-CoV-2 proliferation [ 121 ], although metabolomic analyses revealed that glutamine levels are relatively low [ 8 12 ]. In addition, small clinical trials showed that glutamine reduced the severity after infection in standard risk COVID-19 patients [ 122 , 123 ]; however, these preliminary findings need to be expanded to confidently assess glutamine supplementation in treating COVID-19.…”
Section: Drugs Targeting Hyaluronanmentioning
confidence: 99%
“…Prophylactic glutamine supplementation is recommended to those in high-risk groups; however, glutamine supplementation after the infection should be carefully considered. Glutamine supplementation may favor SARS-CoV-2 proliferation [ 121 ], although metabolomic analyses revealed that glutamine levels are relatively low [ 8 12 ]. In addition, small clinical trials showed that glutamine reduced the severity after infection in standard risk COVID-19 patients [ 122 , 123 ]; however, these preliminary findings need to be expanded to confidently assess glutamine supplementation in treating COVID-19.…”
Section: Drugs Targeting Hyaluronanmentioning
confidence: 99%
“…More importantly, we observed that the infection actively changes both metabolic and proteomic profile. Proteomic analysis of primary astrocytes in vitro, as well as dissected cortex and hippocampus in vivo, demonstrated relevant changes in proteins related to carbon metabolism, biosynthesis of amino acids and the The fact that viruses actively hijack cellular metabolism is well known, as for CMV, HSV, HIV, vaccinia virus, and many others, as reviewed 39 . This occurs either to facilitate viral replication and virion assembling or to evade local immune responses.…”
Section: Discussionmentioning
confidence: 98%
“…ALPK1 and TIFA are closely downstream of rs112641600 and both have adaptive and innate signal transduction roles and pro-inflammatory functions [ 28 ]. MSR1 , upstream of rs118072448, is a macrophage scavenger receptor and implicated in a broad range of disease types including host viral defence [ 29 ] and PSAT1 is associated with glutamine metabolic reprogramming by SARS-CoV-2 and viral mRNA translation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%